Stability of Phycocyanin Extracted from Spirulina maxima in different pH from Indoor and Semi-outdoor Cultivation - Dwi Susilaningsih; Bimo Saskiaoktavian; Ali Djunaedi; Agus Trianto (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2020)
Spirulina maxima is a blue-green microalga that rich in pigment. The pigments in S. maxima grouped into primary pigment (Chlorophyll a) and accessory pigments (carotenoid & phycobiliprotein). Phycocyanin is an accessory pigment that belongs to phycobiliprotein, blue colored, and can be used as natural food coloring and drugs. Phycocyanin has activities as antibacterial, antioxidant, anti-inflammatory, antihyperalgesic, and many more. Because of that, phycocyanin usually used in the pharmaceutical industry. However, phycocyanin is a protein that unstable under lights, high temperature, and pH in the storage. This study aims to obtain information about the effect of pH on the stability of phycocyanin extracted from S. maxima that cultivated in indoor and semi-outdoor. The steps are cultivation, extraction using different solutions to get blue pigment phycocyanin, and stability test. Phycocyanin was dissolved in a buffer solution at pH 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, and 7.0 for 7 days. Color observations based on visualization and concentration measurements are carried out every day to see changes in phycocyanin. Growth in indoor cultivation with 24 hours light is faster than semi-outdoor a that uses only sunlight. Cultivation gets the optical density value 0,6 at day 20 with indoor cultivation and day 34 with semi-outdoor cultivation. Results show that phycocyanin can be extracted using a buffer phosphate solution. The stability of the pigments can be seen from the color changes and relative concentration using a spectrophotometer. Phycocyanin shows stable in the storage of pH 4 until pH 5.5. The highest relative concentration (CR) was shown in pH 5.